The nature of space and time - Hawking, S. W. (Stephen W.); Penrose, Roger (Princeton, N.J. : Princeton University Press, 1996)
Presents essays based on lectures given by mathematics professors Stephen Hawking and Roger Penrose in which they debate the foundations of quantum mechanics, discussing in mathematical and physical terms how to combine quantum theory with the theory of general relativity.
Includes bibliographical references (p. [139]-141).
Choice.
Wilson's Public Library.
Wilson's Senior High School.
Adult
Keywords: Astrophysics; Cosmology; Quantum theory; Space and time; Astrophysics; Quantum theory; Space and time; Universe